Embodying Contagion The Viropolitics of Horror and Desire in Contemporary Discourse - Becker, Sandra; de Bruin-Molé, Megen; Polak, Sara (Horror Studies, 2021)
From Outbreak to The Walking Dead, apocalyptic narratives of infection, contagion and global pandemic are an inescapable part of twenty-first-century popular culture. Yet these fears and fantasies are too virulent to be simply quarantined within fictional texts. The vocabulary and metaphors of outbreak narratives have permeated how news media, policymakers and the general public view the real world and the people within it. In an age where fact and fiction seem increasingly difficult to separate, contagious bodies (and the discourses that contain them) continually blur established boundaries between real and unreal, legitimacy and frivolity, science and the supernatural. Where previous scholarly work has examined the spread of epidemic realities in horror fiction, the essays in this collection also consider how epidemic fantasies and fears influence reality. Initiating dialogue between scholarship from cultural and media studies, and scholarship from the medical humanities and social sciences, this collection gives readers a fuller picture of the viropolitics of contagious bodies in contemporary global culture.